Enhancement of Visible-Light Photocatalytic Activity of Mesoporous Au-TiO2 Nanocomposites by Surface Plasmon Resonance - Minghua Zhou; Jun Zhang; Bei Cheng; Huogen Yu (International Journal of Photoenergy)
Mesoporous Au-TiO2 nanocomposite plasmonic photocatalyst with visible-light photoactivity was prepared by a simple spray hydrolytic method using photoreduction technique at 90∘C. The prepared samples were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, and N2 adsorption-desorption isotherms. The formation of hydroxyl radicals (•OH) on the surface of visible-light illuminated Au-TiO2 nanocomposites was detected by the luminescence technique using terephthalic acid as probe molecules. The photocatalytic activity was evaluated by photocatalytic decolorization of Rhodamine-B (RhB) aqueous solution under visible-light irradiation (λ >  420 nm). The results revealed that the TiO2 could be crystallized via spray hydrolysis method, and the photoreduction technique was facilitated to prepare Au nanoparticles in the mesoporous TiO2 at 90∘C. The light absorption, the formation rate of hydroxyl radicals, and photocatalytic decolorization of Rhodamine-B aqueous solution were significantly enhanced by those embedded Au nanoparticles in the Au-TiO2 nanocomposites. The prepared Au-TiO2 nanocomposites exhibit a highly visible-light photocatalytic activity for photocatalytic degradation of RhB in water, and their photocatalytic activity is higher than that of the pristine TiO2 nanoparticles due to the surface plasmon resonance.